Conference on Lasers and Electro-Optics 2018
DOI: 10.1364/cleo_qels.2018.ff2l.7
|View full text |Cite
|
Sign up to set email alerts
|

Indirect excitons in van der Waals heterostructures at room temperature

Abstract: Indirect excitons (IXs) are explored both for studying quantum Bose gases in semiconductor materials and for the development of excitonic devices. IXs were extensively studied in III-V and II-VI semiconductor heterostructures where IX range of existence has been limited to low temperatures. Here, we present the observation of IXs at room temperature in van der Waals transition metal dichalcogenide (TMD) heterostructures. This is achieved in TMD heterostructures based on monolayers of MoS 2 separated by atomica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
8
1
Order By: Relevance
“…If the IL distance is increased by more than one Angstrom (or alternatively if a single layer of h-BN is inserted between the MoS 2 layers) our ab-initio calculation leads to dark IL excitations. This is in contrast to experiments of Calman et al 23 in which bright IL states have been reported for bilayer MoS 2 with three h-BN spacer layers.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…If the IL distance is increased by more than one Angstrom (or alternatively if a single layer of h-BN is inserted between the MoS 2 layers) our ab-initio calculation leads to dark IL excitations. This is in contrast to experiments of Calman et al 23 in which bright IL states have been reported for bilayer MoS 2 with three h-BN spacer layers.…”
contrasting
confidence: 99%
“…Such CT excitons have been observed in heterobilayers with a natural Type II band alignment[20][21][22] and in bilayer MoS 2 where the Type II band alignment is imposed by an electric field applied perpendicular to the bilayer 23. While the spatial separation of the electron and hole in the CT exciton leads to long lifetimes it also causes a small optical transition matrix element making it challenging to probe by them in absorption and luminescence experiments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…degrees of freedom to engineer their optical and electronic properties. 4,9−14 The vdWHs of transition metal dichalcogenides (TMDs) are particularly exciting for optoelectronic and light-harvesting applications, 14,15 because many monolayer TMDs are direct-bandgap semiconductors with remarkably strong light−matter interactions. 16,17 In the vdWHs, the two constituents with nearly the same lattice constant are overlaid with a relative twist angle of θ, leading to the generation of moireṕ atterns.…”
mentioning
confidence: 99%
“…While in heterobilayers the oscillator strength of IX is weak, the situation can be different for homobilayers or multilayers [13]. In MoS 2 bilayers, strong absorption by IX up to room temperature was reported [14][15][16][17][18][19]. In MoSe 2 , the situation is similar to MoS 2 , though the oscillator strength of the IX is smaller [20].…”
mentioning
confidence: 99%